جودة الخدمات الرياضية فلسفة و ثقافة ؟ أم شهادة و سلوك؟ - عاشور، عادل Ashour, Adel (جامعة زيان عاشور الجلفة - معهد علوم وتقنيات النشاطات البدنية والرياضية, 2022)
أصبحت إدارة الجودة 1 الشاملة في الوقت الحاضر حديث الساعة في أوساط الأعمال والجامعات ومراكز البحث العلمي والشركات العالمية على اختلاف أحجامها في كافة أنحاء العالم وحتى الأجهزة الحكومية أيضا وكافة المؤسسات الخدمية وخصوصا الرياضية منها، والتي أصبحت تحتل فيها الجودة مكانة هامة وأساسية ، فهي أحد أهم الشرايين الحيوية التي تراهن عليها في وضع استراتيجياتها والآليات الهادفة لتحقيق أهدافها من خلال كسب رضا عملائها وولائهم سواء الحاليين أو المرتقبين والمحافظة عليهم من خلال معرفة نتائج جودة الخدمات المقدمة والمدركة لدى زبائنها ومدى تأثير ذلك على رضاهم. وسنشير إلى المعايير العلمية المستخدمة في تطبيق معايير الجودة، سعيا إلى تغذية فكر المستهلك أو العميل والتي بلا شك ستنعكس على ثقافته وسلوكه كمستهلك أو منتج للخدمة، مما يضطر هذه الجهات إلى مواصلة سعيها نحو تطوير خدماتها وفق رغبات واحتياجات بل وتوقعات العميل. Total quality management has become at the present time the talk of the hour in business circles, universities, scientific research centers and international companies of all sizes around the world and even government agencies as well and all service institutions, especially sports ones, in which quality has become an important and essential position, as it is one of the most important vital arteries that are betting on it in developing its strategies and mechanisms aimed at achieving its goals by gaining the satisfaction and loyalty of its customers, whether current or prospective, and maintaining them by knowing the results of the quality of services provided and perceived by its customers and the extent of its impact on their satisfaction. We will tackle to the scientific standards used in the application of quality standards, in an effort to nurture the mind of the consumer or the customer, which will undoubtedly be reflected in his culture and behavior as a consumer or producer of the service, forcing these parties to continue their quest to develop their services according to the desires, needs, and even expectations of the customer.
Keywords: الجودة الشاملة -- الأنشطة الرياضية -- الأداء الوظيفي -- الضبط الجودة